Association between dietary intake, physical activity and stress level with constipation among undergraduate students - Md. Yusop, Nor Baizura; Mohamed Yasin, Nor Qubbul Ain (Persatuan Pemakanan Malaysia, 2021)
Introduction: Constipation is one of the most common health problems among university students. This study aims to determine the association between sociodemographic characteristics, dietary intake, physical activity, and stress level with constipation among undergraduate students. Methods: The study was a crosssectional study and the participants comprised of 140 undergraduate students (27.9% males and 72.1% females). A 3-day dietary record was obtained to determine energy, fibre and fluid intakes, while physical activity was determined using the International Physical Activity Questionnaire. Stress level and constipation were assessed using the Cohen’s Perceived Stress Scale and Agachan’s Constipation Score System Questionnaire, respectively. Data were analysed using IBM SPSS Statistics version 23. Multivariate linear regression analysis was done to determine factors that were associated with constipation. Results: Mean age of the participants was 20.9±1.5 years old and majority were third year students (32.1%). Mean intakes of energy, dietary fibre, and fluids per day were 1567±438kcal, 5.6±3.5g, and 2301±946ml, respectively. The median score for physical activity was 1135.5 METminutes/week. Most of the participants (77.1%) had a high or a very high stress level and 64.3% had slight constipation. Age, dietary fibre, fluid, energy, and perceived stress scale explained a significant amount of the variance in the occurrence of constipation [F(6.133)=16.373, p<0.001, R2=0.425, R2 Adjusted=0.399]. Conclusion: Age, energy, fluid and fibre intakes, as well as perceived stress were factors that were associated with constipation among undergraduate students. Therefore, undergraduate students should be encouraged to practise a healthy lifestyle to modify these identified risk factors.